2020
DOI: 10.4067/s0034-98872020000600724
|View full text |Cite
|
Sign up to set email alerts
|

Infección respiratoria aguda por coronavirus Sars-CoV-2 en personal de salud. Implementación de un programa de detección precoz y seguimiento de casos en un hospital universitario

Abstract: A surveillance system to detect COVID-19 infections in health care workers. Experience in 209 cases Background: Healthcare personnel are a high-risk group for acquiring CO-VID-19 disease. They represent 4 to 20% of the total number of cases reported in different geographical areas. Aim: To describe an epidemiological surveillance strategy to detect symptoms compatible with SARS-CoV-2 infection and early case detection among healthcare personnel at a university hospital. Patients and Methods: We assessed 209 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…These results coincide with those of other studies that report the same self-assessments. A study of health care personnel in Chile found that the majority reported having been in contact with an infected person (patients or coworkers) without adequate protection ( Poblete Umanzor et al, 2020 ). Another study conducted in a hospital in Wuhan found that the main forms of exposure for workers who became infected with COVID-19 were contact with infected patients, contact with infected colleagues and infection in the community ( Lai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results coincide with those of other studies that report the same self-assessments. A study of health care personnel in Chile found that the majority reported having been in contact with an infected person (patients or coworkers) without adequate protection ( Poblete Umanzor et al, 2020 ). Another study conducted in a hospital in Wuhan found that the main forms of exposure for workers who became infected with COVID-19 were contact with infected patients, contact with infected colleagues and infection in the community ( Lai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, protective measures which ensure the safety of workers should be considered a priority not only at present, but also at the onset of future outbreaks ( Chang et al, 2020 ). Considering that the prompt identification of health care personnel with suspected infection and routine examinations in asymptomatic persons are measures that protect the transmission of the virus ( Lai et al, 2020 ), an effective program of early detection of the disease would have allowed the implementation of favorable containment measures to cut the chain of transmission and avoid complications ( Poblete Umanzor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poblete Umanzor R. y cols. 2020 en Santiago de Chile, se observó que el intervalo de tiempo de evolución de los síntomas hasta la toma del examen fue de 3,7 ± 4,1 días de acuerdo a nuestro estudio el inicio de los síntomas y toma de prueba fue de 1,4 días, esta diferencia puede ser por la instalación de el Módulo de Atención Respiratoria del Seguro Social (MARSS), lo cual facilito la toma (63).…”
Section: Tablaunclassified